Mutaciones del cromosoma X en pacientes del sexo femenino del servicio académico , asistencial de genética humana de la UNMSM - Descailleaux, Jaime (2000)
We shall report here the results of the cytogenetic analysis in 124 female patients that had visited the clinic Hospitals because in all the cases they had a gonadal disfunction and/or a deficit in height, 93 women had a normal karyotype (0.75) and 31 (0.25) an abnormal karyotype. The monosomy of the X chromosome 45,X with 16 times (0.52) were the more frequently among the abnonnal karyotypes, followed by the isochromosome of the X long arm with 7 times (0.22), in 3 cases (0.10) the karyotypes were 46,XY and the patients affected by the testicular feminization syndrome, 2 cases (0.06) it were a ring of the X, in 1 case (0,03) a balanced rept (X;X)(q27;q21) and the two others were mosaics with 2 cellular lines. Among the turnerian stigmata the low set nucal hair and the cubitus valgus were the most frequentIy encountered, but the small stature and the gonadal disfunction were always present.